Social And Economic Impacts Of Land Concessions On Rural Communities Of Cambodia: Case Study Of Botum Sakor National Park - Drbohlav, Petr; Hejkrlik, Jiri (Penerbit Universiti Sains Malaysia (USM Press), 2018)
Land grabbing is a serious issue in Cambodia, where land concessions covered approximately 65 percent of the total arable land in 2013. Because of the 36,000-hectare land concession in the Botum Sakor National Park granted by the Cambodian government to a Chinese company, more than 1,400 primarily fshing families have been relocated to new villages built inland, approximately 20 km from the coast. Using a case study research design, this paper provides a unique glimpse into the lives of those relocated by assessing their living conditions, livelihoods, food security, housing and access to basic services approximately four years after the relocation. The results show that those affected by the land concession are worse off than they were before the relocation and will likely remain so in the short to medium term. They have lost their livelihoods, their food and nutrition security have worsened, and their access to both health services and education is problematic.